Screening for cervical abnormalities in antenatal patients with conventional pap smear - K., Krithika; Manoli, Nandish S.; Gupta, Preeti; P., Nishchal Anand (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Cervical cancer screening is crucial for early detection and management of cervical abnormalities, especially in antenatal women who may not regularly undergo such screening. This study assessed the incidence of Pap smear abnormalities among antenatal women at The Oxford Medical College & Hospital. Methods: A descriptive cross-sectional study was conducted over 12 months, involving 114 antenatal women. Pap smear tests were analysed using the Bethesda System 2001 criteria. Data on demographic characteristics, knowledge of cervical cancer, and reasons for not undergoing Pap smear were also collected. Results: The majority of the smears were inflammatory (35.1%), followed by bacterial vaginosis (24.6%) and vaginal candidiasis (14.9%). No high-grade lesions were detected. The mean age of participants was 26.11 years, with a significant portion (39.5%) aged between 21-25 years. Educational status varied, with 29.8% having attained higher education. Knowledge about cervical cancer and Pap smears was low (12.3% and 22.8%, respectively). Socioeconomic factors played a role in screening uptake, with 48.2% belonging to the middle socioeconomic class. Conclusions: The study highlights the absence of high-grade cervical abnormalities among antenatal women in our cohort and underscores the need for integrating cervical cancer screening into routine antenatal care. Addressing educational and psychological barriers could enhance screening uptake.